GC- MS analysis, phytochemical screening, antimicrobial and antioxidant activity of Sudanese annona squmosa seeds oil - Hajer, Tuhami; Mirghani, Mohamed Elwathig Saeed; Mohamed Elnour, Ahmed Adam; Almain, Abdelrahman Ahmed; Mohammed, Manhal Musa Mohammed (IIUM Press, International Islamic University Malaysia, 2018)
The present research was including the phytochemical screening of Annona squmosa seeds in Sudan. Seed samples of Annona squmosa were selected. The objective of this the study was to examine the chemical constituent’s oil of Annona squmosa seeds, Sudan and to assess its potential antibacterial and antioxidant activity. The Oil of Sudanese Annona squmosa seeds were extracted with n-hexane using Soxhlet extractor. Twenty-one components were detected by GC-MS analysis the major constituents are: Hexadecanoic acid (18.48), Heptadecanoic acid Methyl margarate (1.32) (C18H36O2), Heptadecanoic acid Methyl margarate (1.32), 9,12- octadecadienoic acid (Z,Z) (19.29% ), 9 - octadecenoic acid (Z) (34.01%), Methyl stearate (17.12%), Cis-11-Eicosenoic acid (1.14 ) and Eicosanoic acid (3.28% . the results showed that Alkaloids, Flavonoid, Carbohydrate, Saponins, Triterpene, Streol, Tannins and phenolic compounds were present in seeds of the Annona squmosa. According to DPPH assay, the data of oil showed the moderate antioxidant potential (50 ±0.09 compared with standard 93± 0.01). The antibacterial activity of the oil was evaluated by paper disc diffusion assay against six standard human pathogens (Gram-positive Staphylococcus aureus and Bacillus subtilis; Gram-negative: Escherichia coli and Pseudomonas aeruginosa), however, the oil was high activity against Escherichia coli, Bacillus subtilis and Candida albicans organism. The results indicated that oil of none squmosa seeds is a good source of antioxidants due to the presence of phenolic compounds, flavonoids. Also, an excellent source of natural antibacterial and this justify its uses in folkloric medicines.